BETWEEN THE SHARE PRICE OF THE JOINT STOCK COMPANY AND THE EXCHANGE RATE ECONOMIC MODELING OF DEPENDENCY - PhD Tursunxodjayeva Shirin (Scholars Digest Publishing, 2023)
This article assesses the impact of exchange rates on stock prices. For this purpose, the stock prices of the 7-year period from 2016 to 2022 and the exchange rate of the US dollar against the som were taken as the object of analysis.
Keywords: Investment, financial risk, currency risk, stock.